Optimization of Proposal Management Arrangements as Learning Tools in Scientific Research Activities - Harjanto, Rudy; P. Manurung, Edward Boris; Lestari, Arini Dwi (Pandawan, 2018)
For a researcher, compiling or managing a research proposal is a significant step because this step dramatically determines the success or failure of all research activities. For this reason, management is needed from a management research activity, because it is one of the activities that are scientific. Management of research proposals or often referred to as research planning is one example of a management report that is described in detail from the study design that will be carried out to answer existing problems. In a term, there is an understanding of a proposal. It seems that a study is not only intended for individuals because the proposed word implies that something is still waiting for an answer or permission from another party. It is expected that with the management of a scientific research activity management has a clear purpose, which later can be useful as a study material about a matter and most importantly as a reference in making decisions for the benefit of the public or the government or private parties or companies. Keywords: Management, Research, Research Activities